A multimodal stylistic approach to screen adaptations of the work of Alice Munro - Francesconi, Sabrina, 1976- (Routledge, 2023)
"This volume brings together perspectives from multimodal stylistics and adaptation studies for a unified theoretical analysis of adaptations of the work of Alice Munro, demonstrating the affordances of the approach in furthering interdisciplinary research at the intersection of these fields. The book considers films and television programs as complex multimodal stylistic systems in and of themselves in order to pave the way for a clearer understanding of screen adaptations as expressions of modal, medial, and aesthetic change. In focusing on Munro, Francesconi draws attention to a writer whose body of work has been adapted widely across television and film for an international market over several decades, offering a diachronic overview and insights into the confluence of sociocultural contexts, audiences, and dynamics of production and distribution across adaptations. The volume complements this perspective with a microanalysis of the adaptations themselves, exploring the varied creative use of audiovisual dimensions, including sound, light, and movement. The book seeks to overcome simplified fidelity-based understandings of screen adaptations more broadly, showcasing creative multi-layered approaches to a creator's oeuvre to effect true transformation across media and modes. The volume will be of interest to scholars in multimodality, adaptation studies, film studies, and comparative literature"-- Provided by publisher.
"Routledge Focus"--PDF image of cover.
Keywords: Munro, Alice, -- 1931-2024 -- Adaptations.; Munro, Alice, -- 1931-2024 -- Film adaptations.; Munro, Alice, -- 1931-2024 -- Television adaptations.; Munro, Alice, -- 1931-; elektronické knihy; electronic books